IMAJI DAN BAHASA FIGURATIF KUMPULAN PUISI DALAM MAJALAH KARAS EDISI 2022: KAJIAN STILISTIKA - Istiqomah Ramdhaniyah; Imam Safi’i (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2023)
This research aims to describe and collect data empirically about the forms of imagery and figurative language in the poetry collection in the June and December 2022 editions of Karas Magazine. The approach in this research is qualitative. The research method is descriptive because the purpose of this research is to describe the imagery and figurative language in the collection of poems in the June and December 2022 editions of Karas Magazine. The data source in this research is a collection of poems in the June and December 2022 editions of Karas Magazine. Based on the research that has been conducted, the data obtained is that the forms of imagery in the collection of poems in the June and December 2022 editions of Karas Magazine with details on visual or visual imagery as much as 57%, auditive or auditory imagery as much as 27%, thermal or tactile imagery as much as 17%, taste imagery as much as 0%, kinesthetic or motion imagery 0%, and olfactory imagery 0%. The forms of figurative language in the collection of poems in Karas Magazine June and December 2022 editions with details on figurative language of comparison as much as 54%, figurative language of affirmation with the acquisition of 33%, figurative language of opposition as much as 15%, figurative language of satire with the acquisition of 5%. The results of this study can be used as one of the information to find out about the forms of imagery and figurative language in the collection of poetry in the June and December 2022 editions of Karas Magazine.